Penggunaan Quizizz Sebagai Asesmen Formatif Sejarah Kelahiran Pancasila Peserta Didik Kelas VI - Ghoni, Choirudin Abdul; Srinarwati, Dwi Retnani; Zaman, Akhmad Qomaru; Suyono, Suyono (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2026)
This study aims to examine the effect of using Quizizz as a formative assessment instrument on student learning outcomes in the History of the Birth of Pancasila material. Low learning achievement due to monotonous evaluation methods requires the integration of technology in learning. This research applied a quantitative approach with a quasi-experimental method using a Nonequivalent Control Group Design. The population included all seventh-grade students at SMPN 3 Candi Sidoarjo, with sampling conducted via random sampling technique, selecting class VII-8 as the experimental group and class VII-3 as the control group. Data collection instruments consisted of learning outcome tests (pretest and posttest) which were valid and reliable. Data analysis was performed using the Independent Sample T-Test inferential statistic after meeting the normality and homogeneity prerequisite tests. The results showed a significance value (Sig. 2-tailed) of 0.000 (p < 0.05), indicating a significant difference between the two groups. Students who used Quizizz-based assessment obtained significantly higher average learning outcomes compared to students who used conventional assessment. This study concludes that Quizizz is proven effective as an adaptive evaluation alternative and capable of improving student learning outcomes in Pancasila Education subjects.